2017
DOI: 10.1186/s12885-017-3739-x
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-193a-3p is specifically down-regulated and acts as a tumor suppressor in BRAF-mutated colorectal cancer

Abstract: BackgroundThe aim of this study was to identify miRNAs specifically dysregulated in BRAF-mutated colorectal cancer, which could lead to a better understanding of the molecular mechanisms underlying oncogenesis of this malignant subtype of colorectal cancer.MethodsCandidate dysregulated miRNAs were selected in genome-wide miRNA expression array analysis using a screening set composed of 15 BRAF-mutated and 15 non-KRAS/BRAF-mutated colorectal cancers. The miRNA expressions were validated in another set of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…MiR-193a-3p, a member of the miR-193 family, is located at 17q11.2. Recently, it was reported that miR-193a-3p expression was decreased in tumors such as colorectal cancer,17 lung cancer,10 and liver cancer 18. Likewise, we found that miR-193a-3p expression in 37 cases of PDAC tissues was significant lower than in the 42 cases of non-tumor tissues.…”
Section: Discussionsupporting
confidence: 53%
“…MiR-193a-3p, a member of the miR-193 family, is located at 17q11.2. Recently, it was reported that miR-193a-3p expression was decreased in tumors such as colorectal cancer,17 lung cancer,10 and liver cancer 18. Likewise, we found that miR-193a-3p expression in 37 cases of PDAC tissues was significant lower than in the 42 cases of non-tumor tissues.…”
Section: Discussionsupporting
confidence: 53%
“…Two studies from well-regarded groups reported that miR-193a-3p was usually under-expressed in CRC cells and acting as a tumor suppressor 17,20. Our previous report extended their finding by identifying that decreased expression of miR-193a-3p was associated with poor prognosis in CRC 21…”
Section: Discussionmentioning
confidence: 55%
“…Dysregulation of miR-193a-3p, a gene located on human chromosome 17q11.2 (chr17:31,558,803–31,560,358), has been found involved in several cancers including CRC 911. Besides the oncogenic role being reported only in a relatively very few studies,12 almost the vast majority of published data pointed toward a role of miR-193a-3p as tumor suppressor in both solid and blood cancers by targeting targets with potential oncogenic functions to act its tumor cell aggressive inhibiting properties 1317. This contradiction phenomenon also could be seen in studies focused on CRC 1820.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, they participate in extensive biological actions, including cell proliferation, invasion and apoptosis ( 18 , 20 23 ). Previous studies have demonstrated that miR-193a-3p is a neoplasm suppressor in various carcinomas, including hepatocellular cancer ( 24 ), gastric cancer ( 25 , 26 ), lung carcinoma ( 27 ), breast carcinoma ( 28 ) and colorectal carcinoma ( 29 , 30 ). To the best of the authors' knowledge, thus far only one study has investigated the association between miR-193a-3p and medullary thyroid carcinoma ( 31 ); however, a limitation of this study was the small sample size, which prevented a comprehensive description and analysis of TC.…”
Section: Introductionmentioning
confidence: 99%